Tracking transparent monogenean parasites on fish from infection to maturity. Issue 3 (December 2015) - Trujillo-González, Alejandro; Constantinoiu, Constantin C.; Rowe, Richard; Hutson, Kate S.
Abstract: The infection dynamics and distribution of the ectoparasitic fish monogenean Neobenedenia sp. (Monogenea: Capsalidae) throughout its development was examined on barramundi, Lates calcarifer (Bloch) (Latidae), by labelling transparent, ciliated larvae (oncomiracidia) with a fluorescent dye. Replicate fish were each exposed to approximately 50 fluorescent oncomiracidia and then examined for parasites using an epifluorescence stereomicroscope at 10 time intervals post-exposure (15, 30, 60, 120 min, 24, 48 h, four, eight, 12, and 16 days). Fluorescent labelling revealed that parasites attached underneath and on the surface of the scales of host fish. Parasite infection success was 20% within 15 min, and peaked at 93% two days post-exposure, before gradually declining between four and sixteen days. Differences in parasite distribution on L. calcarifer over time provided strong evidence that Neobenedenia sp. larvae settled opportunistically and then migrated to specific microhabitats. Parasites initially attached (<24 h) in greater mean numbers on the body surface (13 ± 1.5) compared to the fins (4 ± 0.42) and head region (2 ± 0.41). Once larvae recruitment had ceased (48 h), there were significantly higher mean post-larvae counts on the head (5 ± 3.4) and fins (12 ± 3) compared to previous time intervals. Neobenedenia sp. aggregated on the eyes, fins, and dorsal and ventral extremities on the main body. As parasites neared sexual maturity, there was a marked aggregation on the fins (22 ± 2.35) compared to the head (4 ± 0.97) and body (9 ± 1.33), indicating that Neobenedenia sp. may form mating aggregations. Graphical abstract: Highlights: Movement of transparent fish monogeneans were tracked using a fluorescent dye. Parasites attach beneath scales of fish, which may affect treatment efficacy. Parasite larvae settled randomly and migrated to preferred microhabitats on the host. The eyes, fins, upper and ventral body surfaces were preferred by the parasite. Neobenedenia sp. aggregated on the fins prior to sexual maturity.